A semantic structuring of educational research using ontologies - Yevhenii B. Shapovalov; Viktor B. Shapovalov; Roman A. Tarasenko; Stanislav A. Usenko; Adrian Paschke (Academy of Cognitive and Natural Sciences, 2021)
This article is devoted to the presentation of the semantic interoperability of research and scientific results through an ontological taxonomy. To achieve this, the principles of systematization and structuration of the scientific/research results in scientometrics databases have been analysed. We use the existing cognitive IT platform Polyhedron and extend it with an ontology-based information model as main contribution. As a proof-of-concept we have modelled two ontological graphs, "Development of a rational way for utilization of methane tank waste at LLC Vasylkivska poultry farm" and "Development a method for utilization of methane tank effluent". Also, for a demonstration of the perspective of ontological systems for a systematization of research and scientific results, the "Hypothesis test system" ontological graph has created.